Pengaruh Variasi Penambahan Starter Bakteri Pseudomonas aeruginosa Terhadap Penurunan Kadar COD, Fosfat dan Detergen pada Air Limbah Laundry - Adila Putri Anindya; Firra Rosariawari; Nurvita Cundaningsih; M. Faisal Fadhil (Jurnal Serambi Engineering, 2025)
The rapid growth of the laundry industry in Indonesia, recorded in 2021 there were more than 30,000 laundries spread throughout Indonesia with a business growth of 15-20% per year (Bisnis et al, 2021) the increased laundry industry means more wastewater will be produced. If it is not treated properly before being discharged into water bodies, it can pollute water bodies and the ecosystems inside. One of the processing methods is the Moving Bed Biofilm Reactor (MBBR) which is a biological method by utilizing microorganisms to form a biofilms and stick to carrier media and then move dynamically so that contact occurs between waste and microorganisms effectively which can degrade pollutants in laundry waste, the more bacteria added and the longer the contact time, the more pollutants will be degraded. In this study, variations in the addition of Pseudomonas aeruginosa bacteria were carried out by 0%, 3%, 5%, 7% and 10% with contact times of 7 hours, 14 hours, 21 hours and 28 hours to degrade COD, phosphate and detergent parameters in laundry wastewater. The greatest removal efficiency was obtained at the addition of 10% bacteria and a contact time of 28 hours, namely 84% COD, 96% detergent and 74% phosphate. The number of colonies in the biofilm with the addition of 0% was 101,000 CFU/mL, 3% was 110,000 CFU/mL, 5% was 184,000 CFU/mL, 7% was 234,000 CFU/mL and 10% was 338,000 CFU/mL.